CONFLICT MANAGEMENT IN EDUCATIONAL ORGANIZATIONS: INNOVATIVE STRATEGIES TO ENHANCE TEACHER AND MANAGEMENT COLLABORATION - Bashori; Jumahir; Esmi Tsalsa Sofiawati (JURNAL PENDIDIKAN GLASSER, 2025)
Conflict in educational organizations is often a major obstacle in achieving institutional goals. This study aims to identify and analyze innovative strategies in conflict management that can improve collaboration between teachers and management in Banggai district. The methodology used was a qualitative approach with in-depth interviews and focus group discussions with education stakeholders. The results showed that open communication strategies, conflict mediation training and the application of information technology in conflict management can significantly reduce tensions and improve cooperation. In addition, adaptive and participatory leadership roles proved effective in creating a harmonious working environment. The practical implication of this research is the importance of developing policies that support proactive and sustainable conflict management. Thus, this study contributes to the literature on conflict management in the context of education and offers practical guidance for education managers in other areas